Análise integrada da paisagem da sub-bacia do rio Pagão-Guararema/Sergipe: um olhar para a fragilidade ambiental - Silveira, Roniex da (2021)
The natural processes of terrestrial dynamics acted and act in the elaboration of the landscapes. With the use of techniques in the organization of space, the social actors resize them and their interventions have repercussions on the biophysical components. Thus, the interest in this study came from the researcher's relationship with the area and from the observation that the types of land use and occupation were not adequate to the characteristics of the geoenvironmental conditions of the landscape, constituting problems, in the medium and long term, for people and the natural dynamics of the sub-basin. Currently, there are methodologies that allow the assessment of the state of the environmental system and support territorial planning, minimizing the negative consequences. Thus, this work aims to analyze the landscape of the PagãoGuararema/SE river sub-basin based on the environmental fragility, expressed in the theoretical-methodological proposal of Ross (1994). For this, bibliographic research, cartographic material survey and field work were carried out. It was found in the landscape the distribution of the following percentages of area for classes of: Potential Fragility – Very Low: 0.62%, Low: 47.80%, Medium: 49.01% and High: 2.46%; and for Emerging Fragility – Very Low: 4.83%, Low: 21.27%, Medium: 71.43% and High: 2.46%. Therefore, Environmental Fragility of Medium category predominates in the sub-basin. The landscape units, tops of the decks and valley bottoms, present Low and Very Low fragility classes due to the weak slope gradient. At the tops, the slope gradient favors infiltration. In the valley bottoms, it interferes in the dynamics conditioned by the proximity of the water table to the surface. In both units, the types of use compete to trigger processes that increase fragility. The slopes and the model dissected into hills and ridges represent the units where the Medium and High fragility classes predominate, due to the greater slope and mass movement processes. In these units, the following types of use dominate – pasture with high trampling, exposed soil and crops without management of conservationist practices. At the mouth of the Pagão-Guararema river, the fluviomarine plain, the fluviomarine and marine terraces fall into the Low and Medium fragility classes, favored by the low slope and textural composition of the sediments. These units are subject to permanent modification by natural processes, and human interventions can produce irreversible imbalances. Still at the mouth, where there are hills whose soils are covered by dense forest, prevailing the Very Low and Low classes. In view of the state of the landscape units of the Pagão-Guararema river sub-basin, it is worth rethinking the organization of productive activities according to the limits of natural components and the way in which social actors have been relating to this landscape.